2021
DOI: 10.3389/fpsyt.2021.716707
|View full text |Cite|
|
Sign up to set email alerts
|

EEG Signal Complexity Is Reduced During Resting-State in Fragile X Syndrome

Abstract: Introduction: Fragile X syndrome (FXS) is a genetic disorder caused by a mutation of the fragile X mental retardation 1 gene (FMR1). FXS is associated with neurophysiological abnormalities, including cortical hyperexcitability. Alterations in electroencephalogram (EEG) resting-state power spectral density (PSD) are well-defined in FXS and were found to be linked to neurodevelopmental delays. Whether non-linear dynamics of the brain signal are also altered remains to be studied.Methods: In this study, resting-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 73 publications
3
18
0
Order By: Relevance
“…This finding is consistent with another preclinical study that showed reduced relative theta power in female Fmr1 KO rats . Clinical studies show decreased cortical alpha (8−13 Hz) power in FXS, ,,, which is similar to our observations of small, but significant, decreases in relative alpha power at baseline in the left somatosensory cortex and auditory cortex in Fmr1 KO mice. Other studies report no alterations in alpha power in Fmr1 KO subjects. ,, The discrepancies could reflect differences in test subject histories and differences in set and setting.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with another preclinical study that showed reduced relative theta power in female Fmr1 KO rats . Clinical studies show decreased cortical alpha (8−13 Hz) power in FXS, ,,, which is similar to our observations of small, but significant, decreases in relative alpha power at baseline in the left somatosensory cortex and auditory cortex in Fmr1 KO mice. Other studies report no alterations in alpha power in Fmr1 KO subjects. ,, The discrepancies could reflect differences in test subject histories and differences in set and setting.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, FPT’s effect of increasing delta power might benefit patients with FXS. However, others report increases in delta power in Fmr1 KO mice and patients with FXS, so it is difficult to make conclusions about the impacts on delta power. There are also irregularities regarding cortical alpha power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also shown in 16p11.2 DEL carriers [66]. Atypical beta and gamma power were found in several neurodevelopmental diagnoses, including ASD [67][68][69] and fragile X syndrome [24,[70][71][72]. Moreover, the increase in beta and gamma power has become a generally accepted marker of schizophrenia [73][74][75].…”
Section: Connectivity Analysissupporting
confidence: 79%
“…The study of resting-state EEG has led to the discovery of deviant brain spectral anomalies and functional organizations in several neurodevelopmental disorders (e.g. [20][21][22][23][24][25][26]). Restingstate EEG has then proven to be an effective method to inform us about the delicate dynamics of neuronal functioning found in neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%